The nonlysosomal β‐glucosidase GBA2 promotes endoplasmic reticulum stress and impairs tumorigenicity of human melanoma cells. Issue 2 (16th October 2012) - Sorli, Sonia‐Caroline; Colié, Sandra; Albinet, Virginie; Dubrac, Alexandre; Touriol, Christian; Guilbaud, Nicolas; Bedia, Carmen; Fabriàs, Gemma; Casas, Josefina; Ségui, Bruno; Levade, Thierry; Andrieu‐Abadie, Nathalie
Abstract : Glycosphingolipids, which are abundant at the surface of melanoma cells, play crucial roles in tumor progression. We investigated whether a newly described glycosphingolipid hydrolase, encoded by the GBA2 gene, can modulate human melanoma cell growth and death. GBA2 expression was quantified on melanoma cells by RT‐qPCR. The antiproliferative effects of GBA2 were assessed in tumor cells expressing inducible GBA2 and in established melanoma xenografts. As a control an inducible catalytically inactive GBA2 mutant was generated. Sphingolipid levels were monitored by mass spectrometry; unfolded protein response (UPR) and apoptosis were assessed by Western blot and flow cytometry analyses, respectively. We report that GBA2 is down‐regulated in melanoma; inducible expression of GBA2 affects endogenous sphingolipid metabolism by promoting glucosylceramide degradation (decrease by 78%) and ceramide generation; this is followed by a UPR that causes apoptosis, subsequent decreased anchorage‐independent cell growth, and reduced in vivo tumor growth (by 40%); and all these events are abrogated when expressing a catalytically inactive GBA2. This study documents for the first time the antitumor activity of GBA2 and provides evidence for the role of nonlysosomal glucosylceramide breakdown as a source of bioactive ceramide and a mechanistic link between glycolipid catabolism and the UPR/death response of melanoma cells.—Sorli, S.‐C., Colié, S., Albinet, V., Dubrac, A., Touriol, C., Guilbaud, N., Bedia, C., Fabriàs, G., Casas, J., Ségui, B., Levade, T., Andrieu‐Abadie, N. The nonlysosomal β‐glucosidase GBA2 promotes endoplasmic reticulum stress and impairs tumorigenicity of human melanoma cells. FASEB J. 27, 489–498 (2013). www.fasebj.org